Effect of liquid liming on sorghum growth in an Ultisol. - Camacho, Manuel E. (2015)
The aim of this study was to evaluate the effects of the application of liquid lime on sorghum growth in an Ultisol. This research was conducted between August and November, 2011 at the Agricultural Research Center, San José, Costa Rica. In an Ultisol planted with sorghum, in pots of 800 ml, the following treatments where applied: control without lime, calcium carbonate at doses of 10 and 20 l/ha, magnesium oxide at doses of 10 and 20 l/ha, calcium carbonate + magnesium oxide at doses of 5 + 5 and 10 + 10 l/ha, respectively. Six weeks after planting, sorghum was harvested, measuring leaf area, dry and fresh weight of the aerial and root biomass, nutrient absorption and the soil chemical characteristics. Treatments using calcium carbonate and calcium carbonate + magnesium oxide obtained the best values of leaf area and the higher weight of the aerial and root biomass of sorghum. Even though there were no significant differences between liquid lime treatments, there were regarding control without lime and weight biomass variables. Liquid calcium carbonate significantly increased Ca absorption, and the calcium carbonate + magnesium oxide treatment at doses of 10 l/h showed the highest Mg absorption. All amendment treatments caused an improvement of the soil fertility, the most notable being the application of 20 l/ha of magnesium oxide that dropped the exchangeable acidity from 9.02 to 0.36 cmol(+)/l, acidity saturation dropped from 95 to 3.3%, and pH increased from 5 to 5.7. It was concluded that the liquid liming amendments had a positive effect over the crop and the soil fertility.